Is Flipped Learning more Effective than Traditional Classrooms in Developing Prospective Elementary Teachers’ Competence of Designing Integrated Natural Science Topics? - Mai, Anh The Hung; Phan, Hoi Thi Thanh; Phan, Duy Duc; Nguyen, Trang Thi Thuy (International Journal of STEM Education for Sustainability, 2022)
The flipped learning has a lot of advantages in university teaching, especially in the era of information technology explosion and in response to the current Covid-19 pandemic. Designing integrated natural science topics (DINST) is an important competence of elementary school teachers in creating an attractive teaching topic with interdisciplinary integration. The purpose of this study is to determine the effectiveness of applying the flipped learning in developing DINST competence compared to applying the traditional teaching model for prospective elementary teachers. The article used a quasi-experimental method. The 86 fourth-year pre-service elementary teachers were divided into two groups in which the experimental group was applied the flipped learning and the control group was done by traditional teaching. This research was conducted in a 7-week course in the semester I (2020 – 21) through the Module of “Scientific Discovery Activities Organization” at one public university of Education in Vietnam. The article has identified the process of organizing teaching to develop DINST competence for future elementary teachers. Pre- and post- tests were designed and applied on both groups. A questionnaire to collect information on the experimental group's learning attitude was also carried out, which helps to further explain our research results. Descriptive statistics and quantitative data analysis were performed on SPSS. The research results have shown that applying the flipped learning has contributed to the development of DINST competence for prospective elementary teachers better than teaching in the traditional way. The research has contributed to proving the positive role of the flipped learning in developing the future Elementary teachers’ competence to integrated teaching and showed that this model can be widely applied in Vietnam's teacher training institutions